Hipertexto e processo formativo: contribuições e/ou obstáculos para a educação. - Lacerda, Fabíola Folchito (Universidade Federal de São Carlos, 2005)
The unbalanced advance between infra-structure and supra-structure, which material base develops at a faster pace than society evolution as a whole, sharply acts on the man who gradually loses awareness about his own significance as an individual, leaving even more fragile those ties binding him to tradition and to a deeper, longer lasting and enhanced knowledge about his history. That was named by Walter Benjamin as experience ( Erfahrung ). The advances in communicational technologies and particularly in Internet and the hypertext, which are reflection matters of this present work, have contributed even more to such unbalance, stimulating a fleeting, a-historical, de-rooted and fragmented living ( Erlebnis ). One of its causes is technical rationality itself, which may be identified on the Internet by speed, ephemerality and informational excess. Those new technologies reach school and, along with the traditional blackboard, chalk and book or study aid material, become part of teaching-learning process. At the computing laboratories, students find out the Internet and at the same face a huge informative, fragmented and non-linearly organized mass - the hypertext. In the optimistic view, electronic hyper-textualiality is the promise of autonomy and motivation besides enriching the training process through accessing information coming from anywhere in the world. The critical ones, on the other hand, analyze the net as one of the newest and most appealing cultural industry expressions, claiming that be a more sophisticated and subtle way to control and oppress, showing that some categories dealt by Adorno and Horkheimer in the last century may be conferred to present time. It was thus through some of those categories such as cultural industry, semi-information and bildung (formation) that investigations have been made to verify in practice to what extend the hypertext offers contributions to education, based on a research carried out at a private school in São Carlos. Students produced compositions about the World War I by means of a traditional research done in the classroom (books, study aid material, notebooks) and using also hypertexts. Analyzing the writings, an under-use of hypertextual resources were noticed, and even an alienation situation, being the text wrote in class of a better use, although presenting mistakes.
Hypertext and the training process: contributions and/or obstacles for education.
Keywords: Métodos de instrução e estudo; Internet; Sistemas hipertexto; Educação; Semi-formação; Hypertext; Internet; Semi-formation; Bildung (formation); Erfahrung (experience); Erlebnis (living); CIENCIAS HUMANAS::EDUCACAO